Mechanics of controlled fragmentation by cold drawing - Li, Dong (2022)
Cold drawing is a mature and widely adopted technique in the shaping of metallic and polymeric materials in industry. Interestingly, cold drawing of a ductile cladding containing a brittle core wire or a ductile substrate supporting a deposited brittle film has recently emerged as a method to produce micron sized rods and ribbons through controlled fragmentation induced by local necking. While this method shows tremendous potential in providing an economic yet efficient technological platform for large-scale manufacturing of structures at the micro- and nanoscale, there is so far no theoretical guideline on how to control the size of the fragmented components. Here, we develop a theory of controlled fragmentation in cold drawing of both axisymmetric core-cladding and plane-strain film-substrate systems. The theory reveals that the process is governed by a reverse shear lag effect which gives rise to a peak tensile stress leading to controlled fragmentation near the necking zone, where the material properties of both the brittle core/film and ductile cladding/substrate play critical roles. Of particular interest is how the feature size of the fragmented components can be reduced toward the nanoscale. To this end, our theory shows that the fragmentation size mainly depends on the interfacial shear strength, geometrical dimension and stiffness of the brittle material, and can be reduced via increasing the strength of interfacial interactions and/or decreasing geometrical dimensions such as the core radius or film thickness.